2019
DOI: 10.1080/14786419.2018.1547292
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition of Erycibe schmidtii and antiproliferative activity of scopoletin on immature dendritic cells

Abstract: Immature dendritic cells (iDCs) play very important roles in the pathological process of rheumatoid arthritis (RA). Therefore, it is urgent to search for natural products with antiproliferative activity on iDCs for anti-RA drug discovery. Erycibe schmidtii, a traditional Chinese medicine, has been used to treat RA in China. Its bioactive ingredients on RA are still unclear. In this study, twenty compounds including a new caffeoylquinic acid derivative, 3-O-caffeoyl-4-O-syringoylquinic acid methyl ester (16), w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…Moreover, caffeoylquinic acid derivatives, also known as strong antioxidant compounds, can effectively treat human leukemia and lung adenocarcinoma by inducing dysfunction of mitochondria [21]. Caffeoylquinic acid derivative also significantly decreased the proliferation level of bone marrow immature dendritic cells, whose function is often disrupted by cancer cells [22,23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, caffeoylquinic acid derivatives, also known as strong antioxidant compounds, can effectively treat human leukemia and lung adenocarcinoma by inducing dysfunction of mitochondria [21]. Caffeoylquinic acid derivative also significantly decreased the proliferation level of bone marrow immature dendritic cells, whose function is often disrupted by cancer cells [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…erefore, DR targeting bone may retard tumor growth and promote anticancer immunity. Sitosterol can ameliorate the state of bone fragility and fracture possibly due to estrogenic modulation [22]. In addition, several studies have indicated that sitosterol inhibit the proliferation of different cultured cancer cell lines such as prostate cancer, ovarian cancer, breast cancer, colon cancer, stomach cancer, leukemia, and lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Fifteen coumarins [compounds 1–6 (Liu et al, 2007), 8 (Feng, Liu, Yang, et al, 2016), 14–15 (Liu et al, 2013), 16 (Liu et al, 2007), 17 (Fan et al, 2015), and 18–21 (Fan et al, 2013; Feng, Liu, Xu, et al, 2016)] have been isolated from E. obtusifolia , while nine coumarins [compounds 1 , 2 , and 7–13 (Song et al, 2010)] have been isolated from E. hainanesis . From E. schmidtii and E. elliptilimba , only two coumarins, scopoletin and scopolin, have been isolated (Lu et al, 1986; Ren et al, 2019; Song et al, 1997). Three bis‐coumarins [compounds 5–6 (Liu et al, 2007) and 7 (Song et al, 2010)] have been isolated from E. obtusifolia and E. hainanesis , among which 7,7′‐dihydroxy‐6,6′‐dimethoxy‐3,3′‐biscoumarin (compound 5 ) and 7,7′‐dihydroxy‐6,6′‐dimethoxy‐8,8′‐biscoumarin (compound 6 ) are relatively rare bis‐coumarins with fully symmetric carbon–carbon bonds.…”
Section: Chemical Compositions Of Erycibes Plantsmentioning
confidence: 99%
“…Currently, 43 quinic acid derivatives have been isolated and identified from Erycibes plants. Among them, 10 quinic acid derivatives [compounds 22 , 25–27 , 33 , and 35–39 (Song et al, 2010)] have been found in E. hainanesis , 32 quinic acid derivatives [compounds 23–24 (Chen, Tao, et al, 2014), 30–32 (Fan et al, 2013), 36 (Fan et al, 2015; Liu et al, 2014), 38–57 (Fan et al, 2013, 2015; Liu et al, 2014), 59–62 (Liu et al, 2014), and 63–64 (Feng, Liu, Yang, et al, 2016)] have been found in E. obtusifolia , and 14 quinic acid derivatives [compounds 22–23 , 25 (Song et al, 1997; Zhou et al, 2016), 28–32 (Ren et al, 2019; Zhou et al, 2016), 34 , 41–43 , 48 , and 58 (Ren et al, 2019)] have been obtained from E. schmidtii . Compounds 22–29 are monocaffeoyl quinic acid and their methyl, ethyl or butyl derivatives; compounds 30–35 and 49–51 are dicaffeoyl quinic acids and their methyl, ethyl or butyl ester derivatives; and compounds 36–48 and 52–64 are bisacylquinic acid derivatives that present different acyl group substitutes of caffeoyl, syringoyl, sinapoyl, and vanilloyl.…”
Section: Chemical Compositions Of Erycibes Plantsmentioning
confidence: 99%
See 1 more Smart Citation